A Preliminary Study on the Influence of Different N and P Levels on the Grain Yield and Some Yield Components of Pearl Millet (Pennisetum glaucum) - BENEK, Azat; GEREN, Hakan (ISPEC Journal of Agricultural Sciences, 2023)
An experiment was conducted to evaluate the effect of fertilization management on growth, yield and yield attributes of pearl millet (Pennisetum glaucum) grown under Mediterranean climatic condition. The experiment was conducted with 25 treatments combination of 5 nitrogen levels (0, 3, 6, 9 and 12 kg N da-1) and 5 phosphorus levels (0, 3, 6, 9 and 12 kg P2O5 da-1) applied through urea and TSP, respectively with 4 replications. Some properties tested in the study such as plant height, thousand grain weight, biological and grain yield. The results indicated that yield attributing parameters of pearl millet crop increased with increasing N levels up to 12 kg N da-1. Effect of P levels also increased yield-attributing characters up to 12 kg P da-1, but increase beyond 9 kg da-1 was not found significant in general. Biological and grain yield of pearl millet increased in a linear fashion with increasing levels of N and P up to 12 kg N and 12 kg P da-1. The combined application of 12 kg N da-1 + 12 kg P da-1 produced maximum grain yield however; it was statistically at par with 9 kg N da-1 + 9 kg P da-1.